ANALYSIS OF FACTORS THAT AFFECT CHINESE PEOPLE’S DECISION OF CHINA STATE-OWNED COMMERCIAL BANKS - Siska Purnama Manurung; Chen Ke (Faculty of Economics and Business, Hasanuddin University, 2018)
The purpose of this study is to examine Chinese people's decision of China state-owned commercial banks, the Chinese people that stay in Greater Jakarta area, Indonesia. The study included four independent variables (service provision, government support, online bank services, bank perceived security) and a dependent variable (Chinese people's decision). Researchers used quantitative studies to study the data, which was collected using questionnaires. A total of 265 questionnaires were valid in this study. Multivariate regression tests were performed using the T test (partial test) and F test (simultaneous test) hypothesis test to analyze the effect of the dependent variable on the dependent variable. Data analysis uses SPSS 20.0 to generate results. The findings of this study that service provision does not have a significant impact on Chinese people's decision, the three variables of government support, online bank services and bank perceived security have a significant impact on Chinese people's decision. At the same time, these three important independent variables provide 41.9% of the dependent variable.